Alterations in serum protein glycopatterns related to small cell lung cancer, adenocarcinoma and squamous carcinoma of the lung. Issue 12 (18th February 2020) - Jia, Liyuan; Ma, Tianran; Liang, Yiqian; Du, Haoqi; Shu, Jian; Liu, Xiawei; Zhang, Zhiwei; Yu, Hanjie; Chen, Mingwei; Li, Zheng
Abstract : The main reason why lung cancer has maintained a high rate of morbidity and mortality is that its early diagnosis is difficult. Abstract : Background : The main reason why lung cancer has maintained a high rate of morbidity and mortality is that its early diagnosis is difficult. No current lung cancer screening is recommended by any major medical organization due to the lack of sensitive and specific screening technologies. Thus, this study aimed to systematically investigate the correlation between the alterations in serum glycosylation and three main types of lung cancers (SCLC, ADC and SqCC). Materials and methods : We investigated the protein glycopatterns in sera from 333 subjects (65 healthy volunteers, 38 benign lung disease patients, 49 small cell lung cancer patients, and 181 NSCLC patients) using a lectin microarray. A serum microarray was produced to evaluate and verify the terminal carbohydrate moieties of the glycoproteins in individual serum samples from 30 cases simultaneously. Results : There were 16 lectins ( e.g., RCA120, BS-I, and UEA-I), 24 lectins ( e.g., HHL, PTL-I, and MAL-II), and 18 lectins ( e.g., GSL-I, LEL, and ACA) that exhibited significant differences in serum protein glycopatterns in the patients with SCLC, ADC and SqCC compared with the controls (HV and BPD). There were 6 lectins ( e.g., EEL, NPA, and LEL) that exhibited significantly increased NFIs in ADC and SqCC compared with SCLC. Also, there were 5 lectins ( e.g., Jacalin, BS-I, and UEA-I) that exhibited significantly decreased NFIs in ADC compared with SCLC and SqCC. Conclusions : This study can facilitate the discovery of potential biomarkers for the differential diagnosis of lung cancer based on the precise alteration in serum protein glycopatterns.